2019
DOI: 10.3390/en12081584
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Current Energy Paradigm and Energy System Models for More Sustainable Energy System Development

Abstract: This study contributes to a better understanding of where to place different energy modelling tools and support better decision-making related to the sustainable development of energy systems. It is argued that through the connection of the energy field and the field of sustainable development, the current energy paradigm—encompassing economic, environmental and social aspects—has emerged. This paper provides an analysis of different categories of existing energy system models and their ability to provide answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Lopion et al (2018) reviewed energy system models and concluded that four elements are required to provide holistic insight for national GHG reduction strategies: 1) cross-sectoral technologies (Pregger et al, 2013;Lopion et al, 2018); 2) high temporal resolution (Lopion et al, 2018;Mallapragada et al, 2018;Victoria et al, 2019); 3) high spatial resolution (Haller et al, 2012;Lopion et al, 2018;Victoria et al, 2019); and 4) evaluating environmental impacts holistically, for which LCA is best suited (Lopion et al, 2018;Ringkjøb et al, 2018). Most energy models reviewed by Lopion et al (2018) aim only for cost-optimal GHG reduction strategies but do not consider other environmental impacts (Spittler et al, 2019), e.g., REMIX (Gils et al, 2017), TIMES (Loulou et al, 2016), and OSeMOSYS (Howells et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lopion et al (2018) reviewed energy system models and concluded that four elements are required to provide holistic insight for national GHG reduction strategies: 1) cross-sectoral technologies (Pregger et al, 2013;Lopion et al, 2018); 2) high temporal resolution (Lopion et al, 2018;Mallapragada et al, 2018;Victoria et al, 2019); 3) high spatial resolution (Haller et al, 2012;Lopion et al, 2018;Victoria et al, 2019); and 4) evaluating environmental impacts holistically, for which LCA is best suited (Lopion et al, 2018;Ringkjøb et al, 2018). Most energy models reviewed by Lopion et al (2018) aim only for cost-optimal GHG reduction strategies but do not consider other environmental impacts (Spittler et al, 2019), e.g., REMIX (Gils et al, 2017), TIMES (Loulou et al, 2016), and OSeMOSYS (Howells et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy is a widely distributed, sustainable source, and its applications are generally environmentally friendly. However, it has a series of serious disadvantages: relatively low energy density, intermittent and uneven distribution [5]. If it is to become one of the main energy suppliers, solar energy must be converted into other forms, such as electricity or heat.…”
Section: Research Background and Significancementioning
confidence: 99%
“…According to Ref. [15], the model landscape can be divided into top-down (economy-wide perspective; limited representation of the energy system), bottom-up (detailed representation of the energy system) and hybrid models (those that include the energy sector as a module), among which different methods (e.g., econometric, optimisation) are used. The distinction between bottom-up and top-down approaches is less conceptual and based more on the different sectoral and technological levels of detail [16].…”
Section: Categorisation Of Techno-economic Energy System Modelsmentioning
confidence: 99%